The Role of Vitamins in DNA Methylation as Dietary Supplements or Neutraceuticals: A Systematic Review - Fareed, Muhammad M.; Ullah, Sana; Qasmi, Maryam; Shityakov, Sergey (Current Molecular Medicine, 2023)
Epigenetic modifications play a vital role in gene regulation associated with different pathologies. Various nutrients in our diet, such as vitamins can modulate these epigenetic mechanism. They also can regulatenderlying pathophysiological factors and processes that directly or indirectly. Most importantly, A, B, C, and D vitamins have recently been shown to be involved in this type of regulation together with vitamins E and K. Despite their effect on the DNA methylation process, an in-depth understanding of vitamin-mediated epigenetic alterations have yet to be investigated. Moreover, the role of vitamins in DNA methylation as nutraceuticals might be important to use for targeted therapy of various human diseases. Overall, this review provides a brief survey of the role of vitamins as epigenetic modulators or nutraceuticals, emphasizing their potential in epigenetic therapy.
Keywords: DNA methylation